COULD TRUST AND RELIGIOSITY AS FACTOR OF INDIVIDUAL TAXPAYER COMPLIANCE?: A SYSTEMATIC LITERATURE REVIEW - Indrawan, Rizki; Setiawan, Amelia; Djajadikerta, Hamfri (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this systematic literature review is to provide information on the implementation, development and factors to tax compliance for individuals by applying PRISMA guidelines. Nineteen published studies were drawn from the most relevant databases. The research topics included in the analysis are trust, religiosity and compliance of individual taxpayers. The synthesis of studies reveals that scientific output has evolved over time and the findings suggest that authorities need to understand and reward taxpayer behavior and recognize the need to provide tax education services as a strategy in improving voluntary compliance and building taxpayer and fiscal trust (Carsamer & Abbam, 2023a). Conclusions on tax compliance from the impact of non-economic factors such as religiosity, the influence of religious values motivate positive behavior of taxpayers in fulfilling tax obligations (Mohdali et al., 2014) Directions for future research on individual taxpayer compliance are also included in this paper.